ASUHAN KEPERAWATAN ANTENATAL CARE (ANC) PADA IBU F DI BIDAN PRAKTIK MANDIRI (BPM) PUJI HANDAYANI SAMARINDA - artika dewi (Husada Mahakam, 2016)
Abstract. Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) in Indonesia is still high, so pemerintahb attempted to care by using obstetric management approach according to Varney. This care using case study design with the documentation in the form of SOAP. The subject of this care is F GII P1001 pregnant women with gestation of 36 weeks and do the collection of physiological data from the anamnesis, physical examination, and investigations using scientific thinking. The method used is the observational method is done by examining a problem through a case study with the primary objective to create a picture or a description of a situation objectively. After doing research, the result that the mother's pregnancy, including low-risk pregnancy care and the results showed that the physiological pregnancy care. The results of this care is not a gap between the theory and the results were made of midwifery care in the pregnancy.